Efektivitas Kinerja Pegawai Dinas Kesehatan dalam Pemberian Vaksin Booster di Kota Pekanbaru - Farah Evrila Rahmadi; Khairul Amri (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Covid-19 is a virus that causes problems in many countries. In Indonesia, the government is making various efforts to overcome the problems caused by Covid-19. In Pekanbaru City the number of people confirmed with Covid-19 is quite high, therefore the Pekanbaru City government continues to accelerate to prevent the spread of the virus. One of the government's efforts to overcome this is to issue a policy of giving booster vaccinations which are useful for achieving a person's herd immunity. This study aims to determine the effectiveness of the Health Office's performance in administering booster vaccines and to find out the inhibiting factors. This study uses the theory of Sedarmayati which consists of 5 indicators namely, Quality of Work, Punctuality, Initiative, Ability and Communication. The method used in this research is a descriptive qualitative research method. With data collection techniques, namely interviews, observation, and documentation. The results of this study are that the effectiveness of the performance of the Health Office in administering booster vaccines can be said to be ineffective because the Health Office carries out health promotion or socialization activities only at the beginning of a pandemic. the vaccines available in Pekanbaru City and the lack of community participation in this matter is what makes the achievement of booster vaccines still relatively low.